PEMASARAN DIGITAL DAN DAYA TARIK WISATA TERHADAP MINAT BERKUNJUNG WISATA TAMBORASI DI KABUPATEN KOLAKA - Sulastry, Helda; Stiadi, Muhamad; Kurniadi, Hanif (LPPM STIE EKA PRASETYA, 2025)
This study aims to determine: (1) The effect of digital marketing on interest in visiting Tamborasi Tourism in Kolaka Regency. (2) The effect of attractiveness on interest in visiting Tamborasi Tourism in Kolaka Regency. This research is a research model that uses a Quantitative approach. Data in this study were acquired by observation, literature study and questionnaire distribution. The population of this research is all residents of Kolaka Regency who are interested in visiting Tamborasi Tourism.Using the purposive sampling technique, the study's sample consisted of 100 respondents. Using SPSS 30.0, validity and reliability tests are used to evaluate research instruments. In order to assess the measurement model (outer model) and the structural model (inner model) using Smart PLS 4.0, the data analysis method employed in this study is Structural Equation Modeling (SEM) based on Partial Least Square (PLS). According to the study's findings, the variable Pemasaran Digital has a significant and positive correlation with Minat Berkunjung, as indicated by its P-Value of 0.009. In addition, a P-Value of 0.008 indicates that the variable Daya Tarik significantly and favorably influences Minat Berkunjung.